Determination of Ginger Simplicial Marketing Strategy in Madura with EFE and IFE Matrix Approach - Widiaswanti Ernaning; Yunitarini Rika; Indriartiningtias Retno (MATEC Web of Conferences, 2022)
Ginger plants have the potential for business to be developed. Part of the ginger plant that is commonly utilized is rhizome. Zingiber rhizome is processed first before storing or selling, one of the ways is in the form of simplicia. Ginger simplicia is often used as a basic ingredient of herbal medicine. Madura Island has a reputation as one of the herbs that have been tested by the National empirical use. Many herbal medicine industries in Madura use ginger simplicia as their raw material. In Madura, ginger simplicia is majorly produced by SMEs. The problems faced by SMEs in Madura are the distribution channels that are not well ordered, lack of venture capital, technology is still very simple, competition with similar businesses both from within and outside the region, and changes in raw material prices. The aim of this research was to formulate a priority marketing strategy for ginger simplicia that can be carried out by SMEs in Madura.The analytical methods used are IFE matrix, EFE matrix, IE matrix, and SWOT matrix. The results of the analysis show 4 priority strategies that can be applied